Distribution of white grubs in three ecological domains of Nepal - Khanal. D.; Yubak Dhoj, G.C.; Sporleder, M.; Thapa, R.B. (Nepal Journals Online, 2012)
A survey was conducted to study the abundance and distribution of white grubs in three districts representing different ecological domines in the country during June-July 2010. Two light traps were installed for two nights in two locations each of Makawanpur, Tanahu and Chitwan districts, and a season long light trap was installed at Mangalpur of Chitwan district from April to September 2010 for assessing scarab beetles flight activity. The ‘simple matching coefficient' revealed high similarity >70% between two sites in each of the districts, while a similarity of 29-50% was observed between sites of different districts. The Jaccard coefficient revealed the same trend. However, coefficients were much lower, above 40% when comparing sites within a district, and below 20% when compared sites among the districts. The dominant species in Chitwan were Anomala dimidiata Hope (24%) followed by Maladera affinis Blanchard (23.75%), Anomala varicolor (Gyllenhal) Rutelinae (23%), Heteronychus lioderus Redtenbacher (14%) and Holotrichia sp (7%). The flight activity and species composition of scarab beetles in the three districts appeared to be different. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 40-46 DOI: http://dx.doi.org/10.3126/aej.v13i0.7586